Pengaruh Green Financing terhadap Efisiensi Operasional Bank Umum Syariah di Indonesia Periode 2020–2024 - Meri Dwi Anggraini; Nova Begawati; Sunreni . (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The increasing adoption of sustainable finance has transformed the orientation of the banking industry from merely pursuing profitability to also considering the environmental and social consequences of financing activities. In Indonesia, the Financial Services Authority (Otoritas Jasa Keuangan/OJK) has actively strengthened sustainable finance regulations, including encouraging Islamic Commercial Banks to develop green financing schemes. As institutions operating based on Islamic values, Islamic Commercial Banks have a moral responsibility to support sustainable development while maintaining operational efficiency. However, the relationship between green financing allocation and operational efficiency remains an issue requiring further empirical investigation. This study aims to examine the extent to which green financing affects the operational efficiency of Islamic Commercial Banks in Indonesia during the period of 2020–2024. Operational efficiency is measured using the Operating Expenses to Operating Income (BOPO) ratio, with the inclusion of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and bank size as control variables. This study employs a quantitative approach using panel data regression analysis on Islamic Commercial Banks that meet the sample selection criteria. The estimation model was determined through a series of tests, including the Chow test, Hausman test, and Lagrange Multiplier test. The Fixed Effect Model estimation results based on 70 panel data observations indicate that green financing has a negative but statistically insignificant effect on BOPO, while CAR, NPF, and bank size are proven to have significant effects on BOPO, with an Adjusted R-squared value of 51.09%. These findings suggest that the contribution of green financing to the operational efficiency of Islamic Commercial Banks in Indonesia has not yet demonstrated a significant impact during the 2020–2024 period, although the direction of the relationship is consistent with theoretical expectations. This study contributes to the growing body of knowledge on sustainable finance and provides practical implications for banking management and regulators in developing green financing strategies that balance environmental sustainability with institutional performance.